Proceedings. Fifth International Symposium on Advanced Research in Asynchronous Circuits and Systems
DOI: 10.1109/async.1999.761523
|View full text |Cite
|
Sign up to set email alerts
|

RAPPID: an asynchronous instruction length decoder

Abstract: This paper describes an investigation of potential advantages and risks of applying an aggressive asynchronous design methodology to Intel Architecture. RAPPID ("Revolving Asynchronous Pentium® Processor Instruction Decoder"), a prototype IA32 instruction length decoding and steering unit, was implemented using self-timed techniques. RAPPID chip was fabricated on a 0.25µ CMOS process and tested successfully. Results show significant advantages-in particular, performance of 2.5-4.5 instructions/nS-with manageab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 11 publications
0
35
0
Order By: Relevance
“…A research group at Intel demonstrated this with their asynchronous instruction length decoder design called RAPPID ("Revolving Asynchronous Pentium Processor c Instruction Decoder") [60]. The RAPPID's length decoding out-performs, by a factor of 3, the same function inside a 400MHz Pentium II fabricated in the identical 0.25µm CMOS process.…”
Section: Large Scale Examplesmentioning
confidence: 99%
See 2 more Smart Citations
“…A research group at Intel demonstrated this with their asynchronous instruction length decoder design called RAPPID ("Revolving Asynchronous Pentium Processor c Instruction Decoder") [60]. The RAPPID's length decoding out-performs, by a factor of 3, the same function inside a 400MHz Pentium II fabricated in the identical 0.25µm CMOS process.…”
Section: Large Scale Examplesmentioning
confidence: 99%
“…Work at Sun Labs [15] shows that asynchronous pipelines, if designed properly, can approach the speed of synchronous shift registers. However, it is unclear if asynchronous pipelines, except in some special cases [60], can ever out-perform synchronous counterparts. A goal is therefore to aim for comparable performance as a synchronous pipeline, but with the added benefits of "elasticity" (variable rate operation).…”
Section: Datapathmentioning
confidence: 99%
See 1 more Smart Citation
“…One potential advantage of asynchronous systems over their clocked counterparts, in certain applications, is better average-case performance [1,19,25]. However, the performance analysis of asynchronous systems remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce these overheads, we propose using relative-timing analysis [15] to optimize these asynchronous implementations by reducing the size of the CD logic. One such system where relative-timing optimizations played a crucial role is the Intel Asynchronous InstructionLength Decoder [13], which was several times faster than its synchronous counterpart. This paper introduces several novel relative-timing algorithms that optimize asynchronous circuits for area.…”
Section: Introductionmentioning
confidence: 99%